Fine mapping of locus Xq25.1-27-2 for a low caries experience phenotype - Küchler, Erika Calvano; Feng, Ping; Deeley, Kathleen; Fitzgerald, Carly A.; Meyer, Chelsea; Gorbunov, Anastasia; Bezamat, Mariana; Reis, Maria Fernanda; Noel, Jacqueline; Kouzbari, M. Zahir; Granjeiro, Jose Mauro; Antunes, Leonardo Santos; et al. (Pergamon-Elsevier Science Ltd., 2014)
Objective: The purpose of this study was to fine map the locus Xq25.1-27-2 in order to identify genetic contributors involved in low caries experience. Design: Seventy-two families from the Philippines were studied. Caries experience was recorded and genomic DNA extracted from peripheral blood was obtained from all subjects. One hundred and twenty-eight polymorphisms in the locus Xq25.1-27-2, a region that contains 24 genes, were genotyped. Association between caries experience and alleles was tested using the transmission disequilibrium test (TOT). This initial analysis was followed by experiments with DNA samples from 1481 subjects from Pittsburgh, 918 children from Brazil, and 275 children from Turkey in order to follow up the results found in the Filipino families. Chi-square or Fisher's exact tests were used. Sequencing of the coding regions and exon-intron boundaries of MST4 and FGF13 were also performed on 91 women from Pittsburgh. Results: Statistically significant association with low caries experience was found for 11 markers in Xq25.1-27-2 in the Filipino families. One marker was in MST4, another marker was in FGF13, and the remaining markers were in intergenic regions. Haplotype analysis also confirmed these results, but the follow up studies with DNA samples from Pittsburgh, Brazil, and Turkey showed associations for a subset of the 11 markers. No coding mutations were identified by sequencing. Conclusions: Our study failed to conclusively demonstrate that genetic factors in Xq25.1-27-2 contribute to caries experience in multiple populations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Caries; Genetics; Linkage Disequilibrium